Engineering reduced graphene oxides with enhanced electrochemical properties through multiple-step reductions. (20th December 2017) - Wei, Min; Qiao, Liang; Zhang, Hanguang; Karakalos, Stavros; Ma, Kuo; Fu, Zheng; Swihart, Mark T.; Wu, Gang
Abstract: Currently, the most prevalent approach to preparing graphene is the oxidation of graphite to graphene oxide (GO) and the subsequent reduction of GO to reduced graphene oxide (rGO). Most reduction methods only focus on one-step reduction by either thermal annealing or chemical reduction. There is no conclusive understanding of which reduction method has advantages over the others. Here, using the same GO precursors, we systematically studied various reduction methods to achieve optimized electrochemical properties. We found that, to improve electrochemical properties of rGO, multiple-step reduction of GO was more effective compared to single-step methods including thermal annealing, microwave treatment, hydrazine reduction, and borohydride reduction. To evaluate the electrochemical performance, rGOs were studied using cyclic voltammetry to evaluate their electrochemically accessible surface area and double layer capacitance. Their steady-state oxygen reduction reaction (ORR) activities were compared in both acidic and alkaline electrolytes to study their potential as the components of ORR electrodes. Among these combinations, two-step borohydride and hydrazine reduction (rGO-NaBH4 -N2 H4 ) with optimal sequence and conditions is able to completely recover the conjugated carbon structure with minimum defects, thus showing the best electrochemical properties. Importantly, extensive physical characterizations including XRD, Raman Spectroscopy, SEM, TEM, BET, and XPS are employed to compare the resulting rGOs in terms of their carbon structures, porosity, surface areas, defect content, and morphologies. These key structural and electrochemical properties of rGOs were found to be largely dependent on the permutation of reduction methods, in turn, affecting electrochemical properties. A correlation of reduction methods, structures, and properties is established to provide knowledge required for engineering rGO through tuning reduction conditions for optimal electrochemical properties for applications. Graphical abstract: Highlights: Multiple-step reduction processes for optimal rGO synthesis enhance electrochemical properties. Comprehensive comparison provide insight into the rGO structures and morphologies. The carbon structures, morphology, porosity, and chemical doping of rGO are tunable by varying the reduction processes. Correlation of reduction, structure and electrochemical properties is established for rGO.